2022
DOI: 10.21203/rs.3.rs-2141400/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between leptin and NAFLD: A Two-Sample Mendelian randomization study

Abstract: Background Nonalcoholic fatty liver disease (NAFLD) etiology involves a complex interaction of genetic and environmental factors. Previous observational studies have suggested that increased leptin levels may be associated with a low risk of developing NAFLD, but the causal relationship remains unclear. Due to advances in genome-wide association studies (GWAS) and the discovery of Mendelian randomization (MR), we aimed to investigate the causal effect of leptin and NAFLD using MR analysis. Methods We perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…It was also found that lithocholic acid in NAFLD rats was much higher than that in normal rats through the regulation of intestinal ora and related lipid/amino acid metabolism, while diosgenin signi cantly reduced lithocholic acid, thus elucidating the mechanism by which diosgenin ameliorates NAFLD[60]. In addition, our ndings showed a bidirectional causal association between bilirubin levels and NAFLD, with an increased risk of NAFLD progression as bilirubin levels increased, which is consistent with our previous ndings [24]. However, there are fewer studies on the direct correlation between bilirubin and NAFLD.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It was also found that lithocholic acid in NAFLD rats was much higher than that in normal rats through the regulation of intestinal ora and related lipid/amino acid metabolism, while diosgenin signi cantly reduced lithocholic acid, thus elucidating the mechanism by which diosgenin ameliorates NAFLD[60]. In addition, our ndings showed a bidirectional causal association between bilirubin levels and NAFLD, with an increased risk of NAFLD progression as bilirubin levels increased, which is consistent with our previous ndings [24]. However, there are fewer studies on the direct correlation between bilirubin and NAFLD.…”
Section: Discussionsupporting
confidence: 90%
“…In particular, metabolomics, a component of systems biology, can provide insight into the biological mechanisms of disease by identifying modi ed metabolites or metabolic pathways.Owing to innovative developments in informatics and analytical technologies, and the integration of orthogonal biological approaches, it is now possible to expand metabolomic analyses to understand the systemslevel effects of metabolites. Moreover, because of the inherent sensitivity of metabolomics, subtle alterations in biological pathways can be detected to provide insight into the mechanisms that underlie various physiological conditions and aberrant processes, including diseases [23].Previously, our team conducted a two-sample MR study [24]. The study involved 7824 participants and this genome-wide association study (GWAS) provided data on 486 human blood metabolites [25].…”
Section: Introductionmentioning
confidence: 99%
“…Further research should explore these potential variations when strati ed GWAS pooled data become accessible. Third, despite the comprehensive sensitivity analyses conducted to test MR study hypotheses, complete elimination of the possibility of horizontal pleiotropy among instrumental variables remains challenging 41 . Moreover, differences in gene annotation analysis platforms across GWAS cohort studies may have contributed to the heterogeneity of this study 42 .…”
Section: Discussionmentioning
confidence: 99%